Effects Reliability, Tangible, Assurance, Responsiveness to Performance HR through Digital Service Quality in Batam Government - Nurhatisyah; Yanti, Sri; Faizah, Ana; Puspita Dewi, Nolla; Wibisono, Chablullah (International Journal of Psychosocial Rehabilitation, 2020)
The word "disruption" has recently become a concern and entered into the line of state institutions, while the 4.0 era is the digital era, where the IR demands governance towards innovation, adaptation, and transparency. The IR 4.0 also requires the government to use a digitalization system in all aspects of services such as e-budgeting, e-learning, e-KTP, e-planning, etc., to what extent the government has prepared quality services, then to support HR in the IR era 4.0. The population of this research is all of the State Civil Apparatuses who take policies in development, amounting to 300 respondents using the formula of Slovin with a sample of 171 respondents. Data evaluation was done using SEM. The platform used for structural analysis is AMOS and SPSS for descriptive research. The results of the study are as follows: reliability, tangible assurance, and responsiveness effect on HR in the IR era 4.0 through positive conventional service quality is not significant.  reliability, tangible, assurance, responsiveness effect on HR in the era of the IR 4.0 through significant positive digital service quality, the effect of conventional service quality on HR in the era of the IR 4.0 positive not significant, affect the quality of digital services to HR in the era of the IR 4.0 was significantly positive. The results of this study indicate that digital services have a significant positive effect; the Government is obliged to build a good e-government system from the center to the entire region, into all institutions, and strengthen technology and communication in order to generate efficiency, effectiveness and productivity while adhering to the principle of accountability and transparency.